A procedure to estimate parameters of a line segment taking into account its representation through π circuits: Theoretical development - Kurokawa, S. [UNESP]; Pissolato, J.; Prado, A. J. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2006)
The objective of this paper is to show an alternative methodology to estimate per unit length parameters of a line segment of a transmission line. With this methodology the line segment parameters can be obtained starting from the phase currents and voltages in receiving and sending end of the line segment. If the line segment is represented as being one or more π circuits whose frequency dependent parameters are considered lumped, its impedance and admittance can be easily expressed as functions of the currents and voltages at the sending and receiving end. Because we are supposing that voltages and currents at the sending and receiving end of the line segment (in frequency domain) are known, it is possible to obtains its impedance and admittance and consequently its per unit length longitudinal and transversal parameters. The procedure will be applied to estimate the longitudinal and transversal parameters of a small segment of a single-phase line that is already built. © 2006 IEEE.
Keywords: Frequency domain; Modal transformation matrix; Phase domain; Transmission line parameters; Frequency domain analysis; Mathematical transformations; Matrix algebra; Parameter estimation; Electric lines